VALIDASI METODE ANALISA PENETAPAN KADAR EPIGALOKATEKIN GALAT DENGAN KROMATOGRAFI CAIR KINERJA TINGGI - Nining Sugihartini; Achmad Fudholi; Suwidjiyo Pramono; Sismindari Sismindari (Universitas Ahmad Dahlan, 2014)
High Performance Liquid Chromatography (HPLC) was one of analytical methods commonly to determine the concentration of epigallocatechin gallate (EGCG) on green tea extract. The method must be validated in order to fit to its purpose. The aim of this research was to prove that the used method has selectifity, liniearity, precise, accurate and know limit of detection (LOD) and limit of quantification (LOQ) is acceptable. The selectifity of analytical method was determined by calculating the resolution value between two peak. Data from 10 ug/ml and 100 ug/ml with 5 replicates would give precition and accuration. Precition was known from CV value and accuration was known from recovery value in each concentration. Liniearity was known from regression linear between concentration and wide area of peak. From regresion linear could calculate LOD and LOQ. Research show that method of analyse have selectificity with Rs= 2,27>1,5; liniearity with r= 0,99; precision with CV 8,74% at concentration 200 µg/ml and 3,74% at concentration 500 µg/ml; accuration with recovery 99,76% at concentration 200 µg/ml and 100,52% at concentration 500 µg/ml and the value of LOD is 33,28 ug/ml and LOQ is 110,93 ug/ml.